Composite particle, positive electrode, all-solid-state battery, and manufacturing method of composite particle
Patent Information
- Application Number
- JP2024119432
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2042-03-17
AI Technical Summary
Sulfide-based all-solid-state batteries face issues with sulfide solid electrolyte deterioration due to direct contact with positive electrode active material particles, leading to increased battery resistance.
Development of a phosphorus-based coating film with a specific composition ratio and inclusion of a glass network forming element and a transition element to promote carrier migration, inhibiting crystallization and reducing resistance.
The phosphorus-based coating film achieves low resistance and durability under high voltage, enhancing the performance of all-solid-state batteries.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to composite particles, positive electrodes, all-solid-state batteries, and methods for producing composite particles. [Background technology]
[0002] Japanese Patent Application Laid-Open No. 2003-338321 (Patent Document 1) discloses forming a film of an inorganic solid electrolyte between a positive electrode material and an organic electrolyte. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2003-338321 Summary of the Invention [Problem to be solved by the invention]
[0004] Sulfide-based all-solid-state batteries (hereinafter abbreviated as "all-solid-state batteries") have been developed. All-solid-state batteries contain a sulfide solid electrolyte. If the sulfide solid electrolyte comes into direct contact with the positive electrode active material particles, the sulfide solid electrolyte may deteriorate. Deterioration of the sulfide solid electrolyte (ion conduction path) may increase battery resistance. Therefore, it has been proposed to form a coating film on the surface of the positive electrode active material particles. The coating film prevents direct contact between the positive electrode active material particles and the sulfide solid electrolyte, thereby reducing the deterioration of the sulfide solid electrolyte.
[0005] Conventionally, LiNbO3 and Li3PO4 are known as materials for coating films. LiNbO3 can have lower resistance than Li3PO4. For this reason, LiNbO3 is becoming more popular. However, according to the new findings of this disclosure, Li3PO4 is superior to LiNbO3 in terms of durability under high voltage. Therefore, the development of a phosphorus-based coating film with low resistance is desired.
[0006] An object of the present disclosure is to provide a phosphorus-based coating film having low resistance. [Means for solving the problem]
[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes speculation. The mechanism of action does not limit the technical scope of the present disclosure.
[0008] 1. The composite particles include positive electrode active material particles and a coating film. The coating film covers at least a portion of the surface of the positive electrode active material particles. The coating film includes a phosphorus compound. The phosphorus compound includes phosphorus and at least one of a first element and a second element. The first element is a glass network-forming element. The second element is a transition element. The composite particles satisfy the relationship of the following formula (1). C Li / (C P +C E1 +C E2 )≦2.5…(1) In the above formula (1), C Li , C P , C E1 , C E2 indicates the element concentration measured by X-ray photoelectron spectroscopy. C Li indicates the elemental concentration of lithium (Li). C P indicates the elemental concentration of phosphorus (P). C E1 indicates the element concentration of the first element (E1). C E2 indicates the element concentration of the second element (E2).
[0009] The Li composition ratio on the surface of the composite particles is thought to reflect the Li composition ratio in the coating film, and can be determined by X-ray photoelectron spectroscopy (XPS).
[0010] In conventional phosphorus-based coating films (Li3PO4), the Li composition ratio is "3.0". + is considered to be a carrier. Therefore, the more carriers there are, the more improved ionic conductivity is expected. In other words, the higher the composition ratio of Li in the phosphorus compound, the more reduced the battery resistance is expected.
[0011] However, according to the new findings of the present disclosure, when the composition ratio of Li in the phosphorus compound is small and a specific element is added to the phosphorus compound, ionic conductivity equal to or greater than that of LiNbO3 can be exhibited. That is, the composite particles satisfy the relationship of the above formula (1), and the phosphorus compound includes at least one element selected from the group consisting of the first element and the second element.
[0012] The first element is a glass network forming element. The first element can form an oxide glass having a network structure by bonding with oxygen (O). The coating film (phosphorus compound) is considered to be an oxide. By adding the first element to the phosphorus compound, for example, "PO x a- ","BO y b- ", "SiO z c- " and multiple types of anions such as " can be generated. The coexistence of multiple types of anions can produce a mixed anion effect. The mixed anion effect can promote the movement of carriers (cations). Furthermore, it is believed that the small amount of carriers further promotes the movement of carriers.
[0013] The second element is a transition element. The transition element has a larger ionic radius than P. Adding the second element to the phosphorus compound can inhibit the crystallization of the phosphorus compound. That is, partial structural defects (disorder) can be introduced into the phosphorus compound. The introduction of structural defects can promote carrier migration. Furthermore, the small amount of carriers is thought to further promote carrier migration.
[0014] Due to the synergistic effects of the above, the phosphorus-based coating film of the present disclosure can have a low resistance equal to or greater than that of LiNbO. The low resistance of the phosphorus-based coating film is expected to achieve both durability under high voltage and high output.
[0015] 2. In the composite particles described in "1." above, the first element may include, for example, at least one element selected from the group consisting of boron (B), silicon (Si), nitrogen (N), sulfur (S), germanium (Ge), and hydrogen (H).
[0016] 3. In the composite particle described in "2." above, the first element may include, for example, at least one element selected from the group consisting of B and Si.
[0017] 4. In the composite particle according to any one of the above items "1." to "3.", the second element may include at least one element selected from the group consisting of second transition elements and third transition elements.
[0018] 5. In the composite particles described in "4." above, the second element may include, for example, at least one selected from the group consisting of lanthanum (La), cerium (Ce), and yttrium (Y).
[0019] 6. The composite particles according to any one of the above items 1 to 5 may have a coverage of, for example, 85% or more. The coverage is measured by XPS.
[0020] A coverage of 85% or more is expected to reduce, for example, battery resistance.
[0021] 7. The positive electrode contains the composite particles according to any one of the above items "1." to "6." and a sulfide solid electrolyte.
[0022] 8. The all-solid-state battery includes the positive electrode described in "7." above.
[0023] 9. A method for producing composite particles includes the following (a) and (b): (a) A mixture is prepared by mixing a coating liquid with positive electrode active material particles. (b) Drying the mixture produces composite particles. The coating liquid includes a solute and a solvent. The solute includes phosphorus and at least one of a first element and a second element. The first element is a glass network forming element. The second element is a transition element.
[0024] The coating liquid adhered to the surface of the positive electrode active material particles dries to form a coating film. The coating liquid described in "9." above can form the coating film described in "1." above.
[0025] 10. In the method for producing composite particles described in "9." above, the solute may contain, for example, a phosphate compound.
[0026] 11. In the method for producing composite particles described in "9." or "10." above, the first element may include, for example, at least one element selected from the group consisting of B, Si, N, S, Ge, and H.
[0027] 12. In the method for producing composite particles described in the above item "11," the first element may include, for example, at least one element selected from the group consisting of B and Si.
[0028] 13. In the method for producing composite particles described in any one of the above items "9." to "12.", the second element may include at least one element selected from the group consisting of second transition elements and third transition elements.
[0029] 14. In the method for producing composite particles described in the above item "13," the second element may include at least one element selected from the group consisting of La, Ce, and Y, for example.
[0030] 15. In the method for producing composite particles according to any one of the above items "9." to "14.", the coating liquid may satisfy, for example, the relationship of the following formula (2). 0.040<(n E1 +n E2 ) / n P ≦1.51…(2) In the above formula (2), n P indicates the molar concentration of P in the coating solution. n E1 indicates the molar concentration of the first element in the coating liquid. n E2 indicates the molar concentration of the second element in the coating liquid.
[0031] "(n E1 +n E2 ) / n P " indicates the molar ratio (ratio of amounts of substances) of the total of the first element (E1) and the second element (E2) to P in the coating solution. When the molar ratio is more than 0.040 and 1.51 or less, a reduction in battery resistance is expected.
[0032] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present example") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure. [Brief explanation of the drawings]
[0033] [Figure 1] FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. [Figure 2] FIG. 2 is a conceptual diagram showing the all-solid-state battery according to this embodiment. [Figure 3] FIG. 3 is a schematic flowchart of the method for producing composite particles in this embodiment. [Figure 4] FIG. 4 is a first graph showing the relationship between the Li composition ratio on the particle surface and the battery resistance. [Figure 5]FIG. 5 is a second graph showing the relationship between the Li composition ratio on the particle surface and the battery resistance. DETAILED DESCRIPTION OF THE INVENTION
[0034] <Definitions of terms, etc.> The terms "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. Open-ended terms may or may not include additional elements in addition to the required elements. The term "consisting of" is closed-ended. However, even closed-ended terms do not exclude additional elements that are normally incidental impurities or unrelated to the disclosed technology. The term "consisting essentially of..." is semi-closed. Semi-closed terms allow for the addition of elements that do not substantially affect the basic and novel characteristics of the disclosed technology.
[0035] "At least one of A and B" includes "A or B" as well as "A and B." "At least one of A and B" can also be written as "A and / or B."
[0036] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0037] Elements expressed in the singular include the plural unless otherwise specified. For example, a "particle" can mean not only a single particle but also an aggregate of particles (powder, powder, particle group).
[0038] Unless otherwise specified, the order of execution of multiple steps, actions, operations, etc. included in various methods is not limited to the order described. For example, multiple steps may proceed simultaneously. For example, multiple steps may occur one after the other.
[0039] For example, unless otherwise specified, a numerical range such as "m to n%" includes both the upper and lower limits. That is, "m to n%" indicates a numerical range of "m% or more and n% or less." Furthermore, "m% or more and n% or less" includes "more than m% and less than n%." Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described elsewhere in this specification, in a table, a figure, or the like.
[0040] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximate values that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measured values may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are made, the more reliable the average value is expected to be. Measured values may be rounded to the nearest significant figure. Measured values may include errors, such as those associated with the detection limits of the measuring device.
[0041] Geometric terms (e.g., "parallel," "perpendicular," and the like) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, and the like in design, work, and manufacturing. The dimensional relationships in each drawing may not match the actual dimensional relationships. To facilitate understanding of the disclosed technology, the dimensional relationships (length, width, thickness, and the like) in each drawing may be changed. Furthermore, some configurations may be omitted.
[0042] When a compound is expressed by a stoichiometric formula (e.g., "LiCoO2"), the stoichiometric formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2," unless otherwise specified, the lithium cobalt oxide is not limited to a composition ratio of "Li / Co / O = 1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping or substitution with trace elements may be permitted.
[0043] "D50" refers to the particle size at which the cumulative frequency from the smaller particle size side reaches 50% in a volume-based particle size distribution. D50 can be measured by a laser diffraction method.
[0044] "Glass network forming element" refers to an element that has glass-forming ability. "Glass forming ability" indicates that the target element can form an oxide glass having a network structure by bonding with O. Hereinafter, the first element may be abbreviated as "E1."
[0045] The term "transition element" refers to an element that exists between Group 3 and Group 11 in the periodic table. Hereinafter, the second element may be abbreviated as "E2".
[0046] <XPS Measurement> (Li composition ratio on particle surface) The composition ratio of Li on the particle surface is Li / (C P +C E1 +C E2 ) can be measured by the following procedure. An XPS instrument is prepared. For example, an XPS instrument manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is placed in the XPS instrument. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, an analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used. The peak area (integral value) of the Li1s spectrum is used to determine the elemental concentration of Li (CLi ) The peak area of the P2p spectrum is converted into the elemental concentration of P (C P For E1 and E2, the appropriate spectrum is selected depending on the type. For example, in the case of B, the peak area of the B1s spectrum is converted to the element concentration of B (C E1 For example, in the case of La, the peak area of the La3d5 spectrum is converted into the element concentration of La (C E2 ) is converted to C P , C E1 and C E2 In total 、 C Li The Li composition ratio on the particle surface is determined by subtracting
[0047] For example, if the coating film contains multiple types of E1, E1 indicates the total element concentration of multiple species of E1, E2 and C E2 The same is true for .
[0048] XPS composition ratio "C Li / (C P +C E1 +C E2 ) reflects the Li composition ratio in the coating film (phosphorus compound), but is not equivalent to the Li composition ratio in the coating film. This is because XPS can also reflect the composition of the base (positive electrode active material particles). For example, if Li in the base is detected in XPS, the Li composition ratio measured by XPS may be higher than the Li composition ratio in the actual coating film.
[0049] (coverage rate) The coverage is also measured by XPS. By analyzing the above measurement data, the ratio of each element (element concentration) can be determined from the peak areas of C1s, O1s, P2p, M2p3, etc. The coverage is calculated using the following formula (3). θ=(P+E1+E2) / (P+E1+E2+M)×100…(3) In the above formula (3), θ represents the coverage (%), and P, E1, E2, and M represent the ratio of each element.
[0050] "M2p3" and M in the above formula (3) are constituent elements of the positive electrode active material particles and represent elements other than Li and O. That is, the positive electrode active material particles may be represented by the following formula (4). LiMO2…(4) M may consist of one element or multiple elements. M may be, for example, at least one element selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), and aluminum (Al). When M contains multiple elements, the total composition ratio of each element may be 1.
[0051] For example, the positive electrode active material particles are "LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2”, the above formula (3) can be transformed into the following formula (3′): θ=(P+E1+E2) / (P+E1+E2+Ni+Co+Mn)×100…(3') In the above formula (3'), Ni represents the element ratio of nickel determined from the peak area of Ni2p3, Co represents the element ratio of cobalt determined from the peak area of Co2p3, and Mn represents the element ratio of manganese determined from the peak area of Mn2p3.
[0052] <Film thickness measurement> The film thickness (thickness of the coating film) can be measured by the following procedure: A sample is prepared by embedding composite particles in a resin material. The sample is cross-sectioned using an ion milling device. For example, an ion milling device manufactured by Hitachi High-Technologies Corporation, product name Arblade (registered trademark) 5000 (or an equivalent product) may be used. The cross-section of the sample is observed using an SEM (Scanning Electron Microscope). For example, an SEM device manufactured by Hitachi High-Technologies Corporation, product name SU8030 (or an equivalent product) may be used. The film thickness is measured in 20 fields of view for each of 10 composite particles. The arithmetic average of the film thicknesses at a total of 200 locations is considered to be the film thickness.
[0053] 《ICP measurement》 The molar ratio in the coating solution (n E1 +n E2 ) / n P " is measured using the following procedure. 100 ml of sample solution is prepared by diluting 0.01 g of coating solution with pure water. Aqueous solutions of P, E1, and E2 (1000 ppm, 10,000 ppm) are prepared. Standard solutions are prepared by diluting 0.01 g of the aqueous solutions with pure water. An ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy) device is prepared. The ICP-AES device measures the emission intensity of the standard solution. A calibration curve is created from the emission intensity of the standard solution. The ICP-AES device measures the emission intensity of the sample solution (diluted solution of coating solution). The mass concentrations of P, E1, and E2 in the coating solution are determined from the emission intensity of the sample solution and the calibration curve. The mass concentrations of P, E1, and E2 are then converted to molar concentrations. The molar concentration of E1 (n E1 ) and the molar concentration of E2 (n E2 ) is the molar concentration of P (n P ) to obtain the molar ratio.
[0054] <Composite particles> FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. The composite particle 5 may be referred to as, for example, a "coated cathode active material." The composite particle 5 includes a cathode active material particle 1 and a coating film 2. The composite particle 5 may form, for example, an aggregate. That is, one composite particle 5 may include two or more cathode active material particles 1. The composite particle 5 may have a D50 of, for example, 1 to 50 μm, 1 to 20 μm, or 5 to 15 μm.
[0055] <Coating film> The coating film 2 is a shell of the composite particle 5. The coating film 2 covers at least a part of the surface of the positive electrode active material particle 1. The coating film 2 contains a phosphorus compound. The phosphorus compound contains P and at least one of E1 and E2.
[0056] The phosphorus compound may further contain, for example, Li, O, carbon (C), etc. P may have a mass fraction of, for example, 1 to 10% relative to the composite particle 5.
[0057] The phosphorus compound may contain, for example, a phosphate skeleton. That is, the phosphorus compound may be a phosphate compound. When the phosphorus compound contains a phosphate skeleton, for example, when the composite particle 5 is analyzed by TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry), it is found that PO2 - or PO3 - Fragments such as:
[0058] The composition ratio of Li on the particle surface is Li / (C P +C E1 +C E2 ) is 2.5 or less (see formula (1) above). When the Li composition ratio is 2.5 or less and at least one of E1 and E2 is present, the battery resistance can be significantly reduced. The Li composition ratio may be, for example, 2.38 or less, 2.26 or less, 2.18 or less, 2.03 or less, 1.89 or less, 1.73 or less, 1.42 or less, or 1.1 or less. The Li composition ratio may be zero. The Li composition ratio may be, for example, 0.1 or more, 0.5 or more, or 1.05 or more. The Li composition ratio may be, for example, 1.05 to 2.38.
[0059] E1 is a glass network forming element. The addition of E1 is expected to produce a mixed anion effect. E1 may contain, for example, at least one element selected from the group consisting of B, Si, N, S, Ge, and H. E1 may contain, for example, at least one element selected from the group consisting of B and Si. E1 may form an oxide glass by itself. E1 may form a complex oxide glass together with P.
[0060] E2 is a transition element. E2 has a larger ionic radius than P. E2 can inhibit the crystallization of a phosphorus compound. E2 may contain, for example, at least one element selected from the group consisting of first transition elements (3d transition elements), second transition elements (4d transition elements), third transition elements (5d and 4f transition elements), and fourth transition elements. E2 may contain, for example, at least one element selected from the group consisting of second transition elements and third transition elements. The third transition elements include lanthanoids. That is, E2 may contain, for example, lanthanoids.
[0061] E2 can be, for example, La, Ce, praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), scandium (Sc), copper (Cu), Y, It may contain at least one selected from the group consisting of zirconium (Zr), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), and gold (Au).
[0062] E2 may contain, for example, at least one selected from the group consisting of La, Ce, Zr, and Y. E2 may contain, for example, at least one selected from the group consisting of La, Ce, and Y.
[0063] The chemical composition of the phosphorus compound may be represented by, for example, the following formula (4): Li w E 1 x E 2 y PO z …(4) In the above formula (4), E 1 indicates E1. E 2 represents E2. w, x, y, and z are arbitrary numbers. w, x, y, and z can be identified, for example, by analyzing the cross section of the composite particle 5 (coating film 2) using STEM-EDX (Scanning Transmission Electron Microscope - Energy Dispersive X-ray Spectroscopy) or the like. The cross-sectional sample is prepared according to the procedure described above in "Film Thickness Measurement."
[0064] The coverage may be, for example, 85% or more. A coverage of 85% or more is expected to reduce battery resistance. The coverage may be, for example, 88% or more, 89% or more, 90% or more, 94% or more, 95% or more, or 97% or more. The coverage may be, for example, 100% or 99% or less. The coverage may be, for example, 85 to 97%, or 90 to 97%.
[0065] The coating film 2 may have a thickness of, for example, 5 to 100 nm, 5 to 50 nm, 10 to 30 nm, or 20 to 30 nm.
[0066] 《Cathode active material particles》 The positive electrode active material particle 1 is the core of the composite particle 5. The positive electrode active material particle 1 may be a secondary particle (aggregate of primary particles). The positive electrode active material particle 1 (secondary particle) may have a D50 of, for example, 1 to 50 μm, 1 to 20 μm, or 5 to 15 μm. The primary particle may have a maximum Feret diameter of, for example, 0.1 to 3 μm.
[0067] The positive electrode active material particles 1 may contain any component. The positive electrode active material particles 1 may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 may contain, for example, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2, Li(Ni 0.5 Co 0.2 Mn 0.3 )O2, Li(Ni 0.8 Co 0.1 Mn 0.1 ) O2, etc.
[0068] <All-solid-state battery> FIG. 2 is a conceptual diagram showing an all-solid-state battery according to this embodiment. The all-solid-state battery 100 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of a metal foil laminate film. The exterior body may house a power generating element 50. The power generating element 50 includes a positive electrode 10, a separator layer 30, and a negative electrode 20. That is, the all-solid-state battery 100 includes the positive electrode 10, the separator layer 30, and the negative electrode 20.
[0069] 《Positive electrode》 The positive electrode 10 is layered. The positive electrode 10 may include, for example, a positive electrode active material layer and a positive electrode current collector. For example, the positive electrode active material layer may be formed by applying a positive electrode mixture to the surface of the positive electrode current collector. The positive electrode current collector may include, for example, an Al foil. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0070] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the separator layer 30. The positive electrode active material layer includes a positive electrode mixture. The positive electrode mixture includes composite particles and a sulfide solid electrolyte. That is, the positive electrode 10 includes composite particles and a sulfide solid electrolyte. Details of the composite particles are as described above.
[0071] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume per 100 parts by volume of the composite particles (positive electrode active material). The sulfide solid electrolyte contains S. The sulfide solid electrolyte may contain, for example, Li, P, and S. The sulfide solid electrolyte may further contain, for example, O, Si, etc. The sulfide solid electrolyte may further contain, for example, a halogen, etc. The sulfide solid electrolyte may further contain, for example, iodine (I), bromine (Br), etc. The sulfide solid electrolyte may be, for example, a glass ceramic type or an argyrodite type. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.
[0072] For example, "LiI-LiBr-Li3PS4" refers to a sulfide solid electrolyte produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the sulfide solid electrolyte may be produced by a mechanochemical method. "Li2S-P2S5" includes Li3PS4. Li3PS4 can be produced, for example, by mixing Li2S and P2S5 in a molar ratio of Li2S / P2S5 = 75 / 25.
[0073] The positive electrode active material layer may further contain, for example, a conductive material. The conductive material can form an electron conduction path within the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass per 100 parts by mass of the composite particles (positive electrode active material). The conductive material may contain any component. The conductive material may contain, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotubes (CNT), and graphene flakes.
[0074] The positive electrode active material layer may further contain, for example, a binder. The amount of binder may be, for example, 0.1 to 10 parts by mass per 100 parts by mass of the composite particles (positive electrode active material). The binder may contain any component. The binder may contain, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene-butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).
[0075] 《Negative electrode》 The negative electrode 20 is layered. The negative electrode 20 may include, for example, a negative electrode active material layer and a negative electrode current collector. For example, the negative electrode active material layer may be formed by applying a negative electrode composite material to the surface of the negative electrode current collector. The negative electrode current collector may include, for example, Cu foil, Ni foil, etc. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0076] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the separator layer 30. The negative electrode active material layer includes a negative electrode composite. The negative electrode composite includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode composite may further include a conductive material and a binder. The sulfide solid electrolytes in the negative electrode composite and the positive electrode composite may be the same or different. The negative electrode active material particles may include any component. The negative electrode active material particles may include, for example, graphite, Si, SiO x (0 <x<2)、およびLi4Ti5O 12 It may contain at least one selected from the group consisting of:
[0077] <<Separator layer>> The separator layer 30 is interposed between the positive electrode 10 and the negative electrode 20. The separator layer 30 separates the positive electrode 10 from the negative electrode 20. The separator layer 30 includes a sulfide solid electrolyte. The separator layer 30 may further include a binder. The sulfide solid electrolytes in the separator layer 30 and the positive electrode composite may be the same or different. The sulfide solid electrolytes in the separator layer 30 and the negative electrode composite may be the same or different.
[0078] <Method of manufacturing composite particles> 3 is a schematic flowchart of a method for producing composite particles according to this embodiment. Hereinafter, "a method for producing composite particles according to this embodiment" may be abbreviated as "the present production method." The present production method includes "(a) preparation of a mixture" and "(b) production of composite particles." The present production method may further include, for example, "(c) heat treatment."
[0079] (a) Preparation of the mixture This manufacturing method includes preparing a mixture by mixing a coating liquid with positive electrode active material particles. Details of the positive electrode active material particles are as described above. The mixture may be, for example, a suspension or a wet powder. For example, a suspension may be formed by dispersing positive electrode active material particles (powder) in a coating liquid. For example, a wet powder may be formed by spraying the coating liquid into the powder. In this manufacturing method, any mixing device, granulating device, etc. may be used.
[0080] The coating liquid contains a solute and a solvent. The solute contains raw materials for the coating film. The coating liquid may further contain, for example, suspended matter (insoluble components), precipitates, etc.
[0081] The amount of solute may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass per 100 parts by mass of solvent. The solvent may contain any component as long as the solute dissolves in it. The solvent may contain, for example, water, alcohol, etc. The solvent may contain, for example, ion-exchanged water, etc.
[0082] The solute includes at least one of E1 and E2 and P. Details of E1 and E2 are as described above. The solute may include, for example, at least one selected from the group consisting of an oxoacid of E1 and an oxide of E1. The solute may include, for example, at least one selected from the group consisting of boric acid, silicic acid, nitric acid, sulfuric acid, and germanic acid. The solute may include, for example, orthoboric acid, metaboric acid, etc.
[0083] The solute may include, for example, an oxide of E2. The solute may include, for example, at least one selected from the group consisting of lanthanum oxide, cerium oxide, and yttrium oxide.
[0084] The solute may include, for example, a phosphoric acid compound, such as phosphoric anhydride (P2O5), orthophosphoric acid, pyrophosphoric acid, or metaphosphoric acid (HPO3)n ] and polyphosphoric acid. The solute may contain, for example, at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid. Metaphosphoric acid and polyphosphoric acid may have longer molecular chains than other phosphate compounds. It is believed that the long molecular chains of the phosphate compound make it easier to produce a coating film with continuity. The continuity of the coating film is expected to, for example, improve the coverage rate.
[0085] The molar ratio of the sum of E1 and E2 to P (n E1 +n E2 ) / n P " may be, for example, more than 0.040 and not more than 1.51 [see formula (2) above]. This is expected to reduce the battery resistance. The molar ratio may be, for example, 1.03 or less, 0.67 or less, 0.48 or less, 0.098 or less, or 0.051 or less. The molar ratio may be, for example, 0.048 or more, or 0.10 or more. The molar ratio may be, for example, 0.048 to 1.03.
[0086] The solute may further include, for example, a lithium compound, such as lithium hydroxide, lithium carbonate, or lithium nitrate.
[0087] The molar ratio of Li to the sum of P, E1, and E2 is "n Li / (n P +n E1 +n E2 The molar ratio "n Li / (n P +n E1 +n E2 )" may be zero, for example. Li may be below the detection limit in ICP measurement. Li / (nP +n E1 +n E2 ) is expected to be smaller, the Li composition ratio on the particle surface is expected to be lower.
[0088] (b) Production of Composite Particles The present production method includes drying the mixture to produce composite particles. The coating solution attached to the surfaces of the positive electrode active material particles is dried to produce a coating film. Any drying method can be used in this production method.
[0089] For example, the composite particles may be formed by a spray-drying method. That is, droplets are formed by spraying a suspension from a nozzle. The droplets contain the positive electrode active material particles and the coating liquid. For example, the composite particles can be formed by drying the droplets with hot air. The use of the spray-drying method is expected to improve, for example, the coverage rate.
[0090] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.
[0091] For example, the composite particles may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) preparation of a mixture" and "(b) production of composite particles" can be carried out simultaneously.
[0092] (c) Heat Treatment The present production method may include subjecting the composite particles to a heat treatment. The heat treatment may fix the coating film. The heat treatment may also be referred to as "baking." Any heat treatment device may be used in the present production method. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air or in an inert atmosphere. [Example]
[0093] <Manufacturing of all-solid-state batteries> Composite particles, positive electrodes, and all-solid-state batteries according to Nos. 1 to 19 were produced as follows. Hereinafter, for example, "composite particles according to No. 1" may be abbreviated as "No. 1."
[0094] No. 1 870.4 parts by mass of hydrogen peroxide solution (30% by mass concentration) were added to the container. Next, 987.4 parts by mass of ion-exchanged water and 44.2 parts by mass of niobic acid (Nb2O5·3H2O) were added to the container. Next, 87.9 parts by mass of ammonia water (28% by mass concentration) were added to the container. The contents of the container were thoroughly stirred to form a solution. This solution is believed to contain a peroxo complex of niobium. Furthermore, 0.1 parts by mass of lithium hydroxide·monohydrate (LiOH·H2O) was dissolved in the solution to prepare the coating solution.
[0095] As the positive electrode active material particles, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2 was prepared. A suspension was prepared by dispersing 50 parts by mass of a powder of positive electrode active material particles in 53.7 parts by mass of a coating liquid. A spray dryer manufactured by BUCHI, product name Mini Spray Dryer B-290, was prepared. The suspension was supplied to the spray dryer to produce a powder of composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 / min. The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. The coating film No. 1 is believed to contain LiNbO3. The coverage was measured using the procedure described above. The measurement results are shown in Table 1 below.
[0096] The following materials were prepared: Sulfide solid electrolyte: 10LiI-15LiBr-75Li3PS4 Conductive material: VGCF Binder: SBR Dispersion medium: heptane Positive electrode current collector: Al foil
[0097] A positive electrode slurry was prepared by mixing the composite particles, sulfide solid electrolyte, conductive material, binder, and dispersion medium. The mixing ratio of the composite particles to the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of conductive material was 3 parts by mass for 100 parts by mass of composite particles. The amount of binder was 3 parts by mass for 100 parts by mass of composite particles. The positive electrode slurry was thoroughly stirred using an ultrasonic homogenizer. A coating film was formed by applying the positive electrode slurry to the surface of a positive electrode current collector. The coating film was dried at 100°C for 30 minutes using a hot plate. A positive electrode blank was thus produced. A disk-shaped positive electrode was cut out from the positive electrode blank. The area of the positive electrode was 1 cm. 2 It was.
[0098] A negative electrode and a separator layer were prepared. The negative electrode active material particles were graphite. The same type of sulfide solid electrolyte was used between the positive electrode, the separator layer, and the negative electrode. A stack was formed by stacking the positive electrode, the separator layer, and the negative electrode in a cylindrical jig. A power generating element was formed by pressing the stack. A terminal was connected to the power generating element to form an all-solid-state battery.
[0099] No.2 A solution was formed by dissolving 10.8 parts by mass of orthophosphoric acid (85%, manufactured by Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 The coating solution was prepared by dissolving lithium nitrate in the solution so that the Li composition ratio "C" was 3.00. After this, composite particles were produced in the same manner as No. 1. The coating film of No. 2 is thought to contain Li3PO4. By the above procedure, the Li composition ratio "C" on the particle surface was determined. Li / (C P +C E1 +CE2 The measurement results are shown in Table 1 below. Furthermore, a positive electrode and an all-solid-state battery were manufactured in the same manner as in No. 1.
[0100] No.3 A solution was formed by dissolving 10.8 parts by mass of orthophosphoric acid (85%, manufactured by Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 The coating solution was prepared by dissolving lithium hydroxide monohydrate in the solution so that the σ (σ) was 0.45. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 3 was, for example, Li x PO y (x, y are arbitrary numbers).
[0101] No.4 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 The coating solution was prepared by dissolving lithium hydroxide monohydrate in the solution so that the σ (σ) was 0.45. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 4 was, for example, Li x PO y (x, y are arbitrary numbers).
[0102] No.5 A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. From this point on, composite particles, a positive electrode, and an all-solid-state battery were manufactured in the same manner as in No. 1. The coating solution No. 5 differs from the coating solution No. 4 in that lithium hydroxide monohydrate was not added. The coating film of No. 5 is formed by, for example, dissolving PO x (where x is any number).
[0103] No.6 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P Boric acid (manufactured by Nacalai Tesque) was dissolved in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 6 was prepared using, for example, B x PO y (x, y are arbitrary numbers).
[0104] No.7 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P Boric acid (manufactured by Nacalai Tesque) was dissolved in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 7 was, for example, B x PO y (x, y are arbitrary numbers).
[0105] No.8 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P Boric acid (manufactured by Nacalai Tesque) was dissolved in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 8 was prepared using, for example, B x PO y (x, y are arbitrary numbers).
[0106] No.9 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P Boric acid (manufactured by Nacalai Tesque) was dissolved in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 9 was, for example, B x PO y (x, y are arbitrary numbers).
[0107] No.10 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P A coating solution was prepared by dissolving lanthanum oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 10 was, for example, La x PO y (x, y are arbitrary numbers).
[0108] No. 11 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P A coating solution was prepared by dissolving lanthanum oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 11 was, for example, La x PO y (x, y are arbitrary numbers).
[0109] No.12 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P Cerium oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 12 was, for example, Ce x PO y (x, y are arbitrary numbers).
[0110] No.13 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 +n E2 ) / n P A coating solution was prepared by dissolving yttrium oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 13 was, for example, Y x PO y (x and y are arbitrary numbers.) In the XPS measurement, the amount of Y detected was negligibly small, so Y was not taken into account in the calculation of the coverage.
[0111] No.14 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. E1 / n P Boric acid (manufactured by Nacalai Tesque) was dissolved in the solution so that the molar ratio "n E2 / n P A coating solution was prepared by dissolving lanthanum oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the molar ratio "(n E1 +n E2 ) / n P The measurement results are shown in Table 1 below. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 14 was, for example, La x B y PO z (x, y, z are arbitrary numbers).
[0112] No.15 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 Lithium hydroxide monohydrate was dissolved in the solution so that the molar ratio (n E1 +n E2 ) / n P Boric acid (manufactured by Nacalai Tesque) was dissolved in the solution so that the value of " was 1.0, thereby preparing a coating solution. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 15 was, for example, Li x B y PO z (x, y, z are arbitrary numbers).
[0113] No.16 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 Lithium hydroxide monohydrate was dissolved in the solution so that the molar ratio (n E1 +n E2 ) / n P A coating solution was prepared by dissolving lanthanum oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the % σ was 0.05. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 16 was, for example, Li x La y PO z (x, y, z are arbitrary numbers).
[0114] No.17 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 Lithium hydroxide monohydrate was dissolved in the solution so that the molar ratio (n E1 +n E2 ) / n P A coating solution was prepared by dissolving cerium oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the % σ was 0.05. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 17 was, for example, Li x Ce y PO z (x, y, z are arbitrary numbers).
[0115] No.18 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 Lithium hydroxide monohydrate was dissolved in the solution so that the molar ratio (n E1 +n E2 ) / n P A coating solution was prepared by dissolving yttrium oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the % σ was 0.05. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 18 was, for example, Li x Y y PO z (x, y, z are arbitrary numbers.) In the XPS measurement, the amount of Y detected was negligibly small, so Y was not taken into account in the calculation of the coverage.
[0116] No.19 A solution was formed by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / (n P +n E1 +n E2 Lithium hydroxide monohydrate was dissolved in the solution so that the molar ratio "n E1 / n P Boric acid (manufactured by Nacalai Tesque) was dissolved in the solution so that the molar ratio "n E2 / n P A coating solution was prepared by dissolving lanthanum oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in the solution so that the % σ was 0.05. After this, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1. The coating film of No. 19 was, for example, Li w La x B y PO z(where w, x, y, z are arbitrary numbers).
[0117] <Evaluation> The battery resistance was measured. The measurement results are shown in Table 1 below. The battery resistance in Table 1 below is a relative value. The battery resistance of No. 1 (LiNbO3) is defined as 1.0. When the battery resistance is 1.2 or less, the coating film is considered to have a low resistance equal to or greater than that of LiNbO3.
[0118] [Table 1]
[0119] <Result> 4 is a first graph showing the relationship between the Li composition ratio at the particle surface and the battery resistance. In the region where the Li composition ratio at the particle surface is 2.5 or less, the battery resistance is significantly reduced.
[0120] Figure 5 is a second graph showing the relationship between the Li composition ratio on the particle surface and the battery resistance. In the region where the Li composition ratio on the particle surface is 2.5 or less, the battery resistance is further reduced by the coating film containing at least one of E1 and E2. When the coating film contains E1 or E2, a battery resistance of 1.2 or less is achieved.
[0121] When the coating film contains both E1 and E2, a battery resistance of less than 1.0 is achieved.
[0122] The present embodiment and examples are illustrative in all respects. The present embodiment and examples are not limiting. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and examples and that they may be combined in any desired manner. [Explanation of symbols]
[0123] 1 Positive electrode active material particle, 2 Coating film, 5 Composite particle, 10 Positive electrode, 20 Negative electrode, 30 Separator layer, 50 Power generating element, 100 All-solid-state battery.
Claims
1. Positive electrode active material particles; A coating film; Including, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film contains a phosphorus compound, The phosphorus compound includes a first element and phosphorus, the first element is boron; The following formula: C Li / (C P +CE1 )≦2.5 Fulfilling the relationship, In the above formula, C Li , C P , C represents the element concentration measured by X-ray photoelectron spectroscopy; C Li indicates the elemental concentration of lithium, C P indicates the elemental concentration of phosphorus, C E1 represents the element concentration of the first element, A coverage rate of 85% or more; The coverage is measured by X-ray photoelectron spectroscopy. composite particles.
2. The phosphorus compound further contains a second element, The second element includes at least one selected from the group consisting of lanthanum, cerium, and yttrium; The following formula: C Li / (C P +C E1 +C E2 )≦2.5 Further satisfying the relationship In the above formula, C Li , C P , C E1 , and C E2 are element concentrations measured by X-ray photoelectron spectroscopy; C Li represents the elemental concentration of lithium, C P represents the elemental concentration of phosphorus; C E1 represents the element concentration of the first element, C E2 represents the element concentration of the second element; The composite particle according to claim 1 .
3. The composite particle according to claim 1 or claim 2 and a sulfide solid electrolyte are included. Positive electrode.
4. The positive electrode according to claim 3, All-solid-state battery.
5. (a) preparing a mixture by mixing a coating liquid and positive electrode active material particles; and (b) drying the mixture to produce composite particles; Including, The coating liquid includes a solute and a solvent, the solute includes a first element and phosphorus; the first element is boron; The coating liquid has the following formula: 0.040<n E1 / n P ≦1.51 Fulfilling the relationship, In the above formula, n P represents the molar concentration of phosphorus in the coating liquid; n E1 represents the molar concentration of the first element in the coating liquid; A method for producing composite particles.